Connected from Afar: Culturally Grounded Remote Peer Support During the COVID-19 Pandemic - Chen, Emma; Liu, Yina (Journal of the Canadian Association for Curriculum Studies, 2024)
In this article, two PhD students from separate Canadian universities, both sharing an immigrant background, engage in autobiographical narrative inquiry, highlighting the importance of peer-support experiences during the pandemic. They explore their journeys as immigrants and PhD students, recounting their experiences in a virtual support group. This narrative illustrates the exchange of academic, mental health and personal support rooted in shared culture, language and ethnicity. The study provides insights into the benefits of peer support on virtual platforms and adds immigrant perspectives. It suggests that university administrators can find innovative ways to support marginalized students, fostering mutual support among them, particularly in the remote-learning context of COVID. This article highlights the potential for authentic and effective support systems that address the unique challenges faced by immigrant and marginalized students, enhancing their academic and personal development.